2022
DOI: 10.1136/bmjgh-2021-007990
|View full text |Cite
|
Sign up to set email alerts
|

‘Writing budgets for meetings and teas?’: a multitheoretical analysis of intragovernmental coordination for multisectoral action for health in Uganda

Abstract: IntroductionCoordination across policy domains and among government agencies is considered critical for addressing complex challenges such as inequities, urbanisation and climate change. However, the factors influencing coordination among government entities in low-income and middle-income countries are not well known. Although theory building is well suited to explain complex social phenomena, theory-based health policy and systems studies are limited. This paper examined the factors influencing coordination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Central-level agencies such as the OPM and NPA were constrained, despite clear mandates, by limited technical capacity and non-material resources such as legitimacy. This is consistent with other assessments (Secretariat, 2013;A et al, 2016;Roberts and Ssejjaaka, 2017;Ssennyonjo et al, 2022) and with literature from LMICs emphasising the importance of relational and technical factors (Hongoro, Akim J and Kembo, 2012;Zaidi et al, 2018;Mahlangu, Goudge and Vearey, 2019).…”
Section: Emerging Insights and Implications For Multisectoral Action ...supporting
confidence: 90%
See 2 more Smart Citations
“…Central-level agencies such as the OPM and NPA were constrained, despite clear mandates, by limited technical capacity and non-material resources such as legitimacy. This is consistent with other assessments (Secretariat, 2013;A et al, 2016;Roberts and Ssejjaaka, 2017;Ssennyonjo et al, 2022) and with literature from LMICs emphasising the importance of relational and technical factors (Hongoro, Akim J and Kembo, 2012;Zaidi et al, 2018;Mahlangu, Goudge and Vearey, 2019).…”
Section: Emerging Insights and Implications For Multisectoral Action ...supporting
confidence: 90%
“…Our study revealed that market-based tools were generally absent at the central government level, despite recent global trends such as the pursuit of result-based management approaches in Africa underpinned by neoliberal market logic (African Development Bank 2017, Oxman andFretheim 2009). The Ugandan context (like other LMIC) is characterized by challenges in performance measurement, risk-averse principals, weak capacity to monitor, high transaction costs, strong interdependence, high complexity and uncertainty (Roberts and Ssejjaaka, 2017;Uganda Ministry of Public Service, 2017;Mukuru et al, 2021;Ssennyonjo et al, 2022). These features favour dominance of tools based on hierarchical and network-based mechanisms as per the TCE and PAT theories ( (Rossignoli and Ricciardi, 2015) Additionally, lack of market based tools can be explained by notions of the path-dependence in institutional change (Thelen, 1999).…”
Section: Emerging Insights and Implications For Multisectoral Action ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The framework focuses on coordination within government and between government and non-state actors such as donors. The framework assumes that poor coordination occurs when there is (1) misalignment, (2) duplication, or (3) fragmentation of institutional structure and implementation processes in the health sector [13,[17][18][19]. Misalignment occurs when multiple health system structures or processes do not yield coherent incentives and outcomes.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The framework focuses on coordination within government and between government and non-state actors such as donors. The framework assumes that poor co-ordination occurs when there is 1) misalignment, 2) duplication, or 3) fragmentation of institutional structure and implementation processes in the health sector [13,[17][18][19].…”
Section: Conceptual Frameworkmentioning
confidence: 99%